The determinants of self-employment intention among public universities students towards sustaining financial capacity - Yahaya, Siti Norbaya; Bakar, Mohd Hafiz; Ahmad Murad, Murzidah; Lau, Kelson; Ghazali, Aziatul Waznah (Malque Publishing, 2025)
This study investigates the determinants of self-employment intention among public university students in Malaysia. The study aims to understand the factors influencing students’ inclination towards self-employment, with a focus on attitude towards behaviour, perceived behavioural control, and entrepreneurial education as potential determinants. This study utilised a cross-sectional design and quantitative approach to investigate the self-employment intentions of 377 students from public universities in Malaysia. Stringent measures, such as pilot testing and reliability analysis, were implemented to ensure the reliability of the data. Statistical analysis, conducted using SPSS, explored the associations between various factors and self-employment intentions through descriptive statistics, Pearson’s correlation coefficient, and multiple regression analysis. Attitude towards self-employment and perceived behavioural control play a significant role in influencing self-employment intention among public university students in Malaysia. Entrepreneurial education does not have a direct influence on self employment intentions among public university students in Malaysia. This study addresses the necessity of identifying the key determinants that have a notable impact on shaping the self-employment intention of public university students. The result will assist policymakers and higher education institutions in formulating an appropriate policy and program to encourage self-employment among public university graduates.